Konsep E-Tourism Dalam Pengembangan Pariwisata Era Modern - Kurniawan, Ramdhan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of writing this work is to understand the concept of e-tourism in the development of modern era tourism. The research method used to explore the concept of E-Tourism in modern era tourism development involves a literature review of relevant journal articles, books and recent reports. A literature search was carried out systematically using relevant keywords, such as "E-Tourism" and "Tourism Development". Statistical data from national and international tourism organizations is also used to support analysis of trends and impacts of tourism development. Data collection techniques include literature studies, document analysis, and interviews with tourism and information technology experts to gain additional insights. The urgency of tourism in Indonesia is manifested in its vital economic role, demonstrated by the Ministry of Culture and Tourism of the Republic of Indonesia in strengthening community welfare through sustainable tourism practices. Tourism potential is driven by Indonesia's natural wealth, strengthened by the role of information technology, but requires collaboration between the government, society and the private sector to optimize its impact on the economy, culture and the environment. E-Tourism concept, improving tourism accessibility and visibility with internet technology. Personalized travel experiences and cost efficiency attract tourists, but the importance of considering environmental sustainability in the implementation of E-Tourism is also an important key in the development of modern tourism.